Auditory Midbrain Hypoplasia and Dysmorphology after Prenatal Valproic Acid Exposure. (1st January 2019) - Mansour, Yusra; Mangold, Sarah; Chosky, Devon; Kulesza, Randy J.
Highlights: In utero exposure to VPA results in an increased risk of ASD in humans. VPA exposure resulted in fewer neurons in the NLL and CNIC. VPA exposure resulted in fewer CB+ neurons in the DNLL and smaller CB+ axons. VPA exposure resulted in decreased dopaminergic innervation to the CNIC. Abstract: Prenatal exposure to the antiepileptic valproic acid (VPA) is associated with an increased risk of autism spectrum disorder (ASD) in humans and is used as an animal model of ASD. The majority of individuals with ASD exhibit adverse reactions to sensory stimuli and auditory dysfunction. Previous studies of animals exposed to VPA reveal abnormal neuronal responses to sound and mapping of sound frequency in the cerebral cortex and hyperactivation, hypoplasia and abnormal neuronal morphology in the cochlear nuclei (CN) and superior olivary complex (SOC). Herein, we examine the neuronal populations in the lateral lemniscus and inferior colliculus in animals exposed in utero to VPA. We used a combination of morphometric techniques, histochemistry and immunofluorescence to examine the nuclei of the lateral lemniscus (NLL) and the central nucleus of the inferior colliculus (CNIC). We found that the VPA exposure resulted in larger neurons in the CNIC and the dorsal nucleus of the lateral lemniscus (DNLL). However, we found that there were significantly fewer neurons throughout all nuclei examined in the auditory brainstem of VPA-exposed animals. Additionally, we found significantly fewer calbindin-immunopositive neurons in the DNLL. VPA exposure had no impact on the proportions of perineuronal nets in the NLL or CNIC. Finally, consistent with our observations in the CN and SOC, VPA exposure resulted in fewer dopaminergic terminals in the CNIC. Together, these results indicate that in utero VPA exposure significantly impacts structure and function of nearly the entire central auditory pathway.